Steps towards improving the system of records, collection and monitoring of data relevant to statistics within the system of juvenile justice in the Republic of Serbia - Stevanović Ivana (Temida, 2012)
The paper emphasises the importance of „good statistics of juvenile justice“ as one of the basis for a clearer overview of the juvenile crime situation, in order to create unique policies at local and national levels for the suppression and prevention of this phenomenon, and to create appropriate areas for action in terms of improving the system reform. The author particularly gives a review of the „Global Indicators in Juvenile Justice“ which present the basic set of data and comparative tool that provides a basis for the assessment and evaluation of services and policies in the field of juvenile justice, and highlights the importance of compatibility of „national indicators“ with them. Particular attention in the paper has been devoted to the overview and analysis of the necessary measures to improve this field, that were prepared and delivered to the relevant ministries and institutions by the Council for Monitoring and Promoting the work of Bodies Engaged in Criminal Proceeding and Enforcement of Juvenile Criminal Sanctions Involving Juveniles - Juvenile Justice Council (hereinafter: the Council). It was pointed, first of all, at the suggestions made by the Council to the Ministry of Justice with the aim to improve the Program for automated record keeping, at the necessary changes of the Court rules, and certain amendments to Forms SK- 3 and SK- 4 of the Statistical Office of the Republic of Serbia were presented. [Projekat Ministarstva nauke Republike Srbije, br. 47011: Kriminal u Srbiji - fenomenologija, rizici i mogućnosti socijalne intervencije]